Environmental, Social, and Governance Performance and Investment Efficiency: The Energy Sector Indonesia - Tumba, Afnei Ngan Billy (Universitas Indo Global Mandiri, 2024)
Environmental, Social, and Governance (ESG) has become an interesting issue in corporate sustainability reports in Indonesia, awareness of the importance of the environment in the business chain encourages companies in the energy sector in Indonesia to start implementing it, the impact of ESG strategies and operations on company performance is a topic of discussion in modern academic and business research today. Researchers also look at the efficiency of corporate investment. Companies in the energy sector are required to implement ESG in their business chain, what about the investment efficiency that occurs in energy sector companies that are directly involved in the issue of environmental problems caused in the company's operational activities. The purpose of this study is to analyze the effect of investment efficiency and ESG performance on company performance in the energy sector listed on the Indonesia Stock Exchange (IDX). The method is used the Hodrick-Prescott Filter to determine investment efficiency and ESG Score as data to see ESG performance. The samples used in this study are energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019-2023 that have ESG Score. The main result is the effect of ESG performance and corporate investment efficiency affect the performance of energy sector companies in Indonesia. The conclusion of this study will contribute to energy sector companies in Indonesia in the practice of implementing ESG and forming investment efficiency strategies in the business chain for company performance in Indonesia. Keywords: ESG, investment efficiency, firm performance, hodrick-prescott filter.